UPTAKE AND METABOLISM OF INDIVIDUAL POLYBROMINATED DIPHENYL ETHER CONGENERS BY EMBRYONIC ZEBRAFISH. (1st April 2013) - Usenko, Crystal Y.; Robinson, Eleanor M.; Bruce, Erica D.; Usenko, Sascha
Abstract Embryonic zebrafish were used to compare the uptake and metabolism of six polybrominated diphenyl ether (PBDE) congeners (BDEs 28, 47, 99, 100, 153, and 183) and identified metabolites from static exposures at 24 and 120 h postfertilization (hpf). An inverse relationship was observed between uptake of PBDEs and their octanol–water partitioning coefficients (uptake of BDEs 28 and 47 > 99 and 100 > 153 and 183). Debromination metabolites were identified in all congeners (excluding BDE 28) tested in the 120‐hpf tissue samples. Interestingly, BDE 153 underwent meta‐debromination, forming BDEs 47 and 99. Gene transcription analysis was conducted at 120 hpf to identify potential metabolic pathways for the PBDEs examined in the present study (gstpi, deiodinases 1 and 2, cyp1a1, cyp1b1, and ugt5g). The greatest induction was of ugt5g for all congeners and deiodinase transcription was also upregulated by BDEs 28, 47, and 183. The cyp1a1 and cyp1b1 were upregulated by BDEs 28, 47, 99, and 183. The least alterations in gene transcription were in the BDE 153–exposed embryos. A clear primary pathway of debromination metabolism was not identified; however, upregulation of these different genes indicated that fish were responding to exposure of PBDEs. Furthermore, the present study demonstrated that the most bioavailable congeners are also those with the highest reported toxicity. Environ. Toxicol. Chem. 2013;32:1153–1160. © 2013 SETAC